2018
DOI: 10.1007/s10067-018-4177-0
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis associated with immune checkpoint inhibitors—a systematic review

Abstract: Recent experimental and genetic studies have implicated the role of programmed cell death protein 1 (PD-1), programmed cell death protein-ligand 1 (PDL-1), and cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) in the pathogenesis of medium and large vessel vasculitis. This study sought to evaluate the occurrence and nature of vasculitis associated with cancer treatment using immune checkpoint inhibition (anti-PD-1, anti-PDL-1, and anti-CTLA4). A systematic review of the medical literature was conducted by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
138
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(144 citation statements)
references
References 33 publications
1
138
0
5
Order By: Relevance
“…More rarely, immune‐related peripheral neuropathies may manifest as isolated cranial neuropathies, lumbar or brachial plexopathy, enteric plexus neuropathy, or peripheral nervous system vasculitis …”
Section: Clinical Syndromes and Presentationsmentioning
confidence: 99%
“…More rarely, immune‐related peripheral neuropathies may manifest as isolated cranial neuropathies, lumbar or brachial plexopathy, enteric plexus neuropathy, or peripheral nervous system vasculitis …”
Section: Clinical Syndromes and Presentationsmentioning
confidence: 99%
“…Granulomatous reactions are a rare subset of IRAEs that develop in response to checkpoint inhibition. An extensive literature search found several articles documenting cases of granulomatous IRAEs . Many of these cases were diagnosed as sarcoidosis in response to ipilimumab monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…On average, the cutaneous eruption resolved 21 weeks after therapy discontinuation . In terms of vasculitis, to date, there have been 20 confirmed cases of vasculitis associated with immune‐checkpoint inhibitors . Of these cases, one was diagnosed as granulomatous vasculitis in response to ipilimumab …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review of all rheumatic adverse events caused by ICPis, vasculitis was reported in two clinical trials, and reports were otherwise limited to case reports . Another review identified 53 cases of vasculitis associated with the use of an ICPi, of which 20 were confirmed cases . Small‐, medium‐, and large‐vessel vasculitides affecting numerous organs including the skin, large vessels, and peripheral nerves have been reported .…”
Section: Rheumatic Toxicitymentioning
confidence: 99%